Evaluasi Program Pendidikan: Training Program Evaluation Model Krikpatrick - Sukeriyadi, Mutmainnah; Zurqoni; Sugeng (Sekolah Tinggi Ilmu Tarbiyah Syamsul Ma'arif Bontang, 2024)
Evaluation of education and training programs is a crucial aspect of human resource development. This program discusses the use of the Kirkpatrick Model in Training Program Evaluation (TPE) within the context of the Substantive Religious Moderation Technical Training Batch I in 2019. The objective of this training is to enhance the knowledge, skills, and attitudes of the participants. The target of this training is Civil Servant Religious Counselors in South Sulawesi, West Sulawesi, North Sulawesi, and Central Sulawesi. The program also discusses assessment instruments from superiors, peers, and trainers towards the alumni of the training, as well as the results of data analysis showing a positive impact on the performance of the alumni. Additionally, the document discusses training evaluation models such as the Kirkpatrick model, which provides a framework for measuring the effectiveness, efficiency, and impact of training programs. This model has four levels: reaction, learning, behavior, and results/outcomes, which help organizations collect data, analyze results, and make appropriate decisions to optimize training strategies. The program also addresses the strengths and weaknesses of TPE using the Kirkpatrick model and concludes with the importance of evaluating educational programs. Educational program evaluation helps organizations determine the benefits of the program for participants and the organization as a whole. Training Program Evaluation is essential to ensure the program provides benefits for participants and the organization. Thus, it will provide a comprehensive understanding of educational and training program evaluation, with an emphasis on the importance of evaluation to ensure the program's benefits for participants and the organization as a whole.